Psycho-oncology: History, Current Status, and Future Directions in Japan - Akechi, Tatsuo (JMA J, 2018)
One of the most relevant risk factors for cancer is aging; thus, the number of patients who develop cancer and die is increasing in Japan. Cancer has been a leading cause of death since 1981, and more than one-fourth of Japanese people die of cancer. More than 1,000,000 and 37,000 Japanese people develop cancer and die every year, respectively, making it a major health problem in Japan. Psycho-oncology is a relatively new medical field that was established in the 1970s in Western countries and introduced in Japan in the 1980s. Psycho-oncology was developed for investigating two issues neglected in previous medical research: the impact of behavioral and psychosocial factors on cancer morbidity and mortality and the psychological influence of cancer on patients, their families, and medical staff. Because of progress made in cancer treatment, cancer diagnosis is not necessarily equivalent to a death sentence. However, approximately half of patients with cancer die, and many patients with cancer and their families need appropriate care for psychological distress. The most common psychiatric problems patients with cancer experience are adjustment disorders, major depression, and/or delirium. In addition, the suicide rate in Japan for individuals within 1 year of a cancer diagnosis is more than 20 times higher than that for individuals without cancer. Physical symptoms, such as pain and nausea/vomiting, can be closely associated with psychological function. Mental health professionals, particularly psycho-oncologists, are expected to work with other cancer professionals to manage patients' distress. The present review focuses on patients with cancer' psychological distress and physical symptoms that are closely associated with psychological function and provides an overview of the current status of psycho-oncology in Japan. The future perspective of psycho-oncology is also discussed.